Behcet’s Disease with Absent HLA Serotyping and Pathergy Test - Ranabhat, S.; Byanju, R.; Khadka, S. (Kathmandu University Medical Journal, 2021)
Behcet’s disease is a multisystemic vasculitis of unknown etiopathogenesis characterized by recurrent acute inflammation. A 30-year male presented with progressive blurred vision in both eye for one month associated with photophobia, redness and ocular pain. On presentation best corrected visual acuity was 6/9 both eyes. Bilateral ocular examination of anterior segment demonstrated occasional cells. Treatment history of multiple joint pain along with oral aphthous ulcers. Erythematous papulopustular lesion over face, neck, trunk and genital ulcers were being treated. Irrespective of negative human leucocyte antigen B51 and pathergy, patient was diagnosed as Behcet’s disease on the basis of clinical criteria and started with topical steroid and cycloplegic. At one-month, ocular symptoms were relieved. Behcet’s disease is a rare, autoimmune disease, which lacks universal pathognomonic test and investigations, therefore diagnosis is primarily done with international criteria for Behcet’s disease. Multidisciplinary approach certainly helps in early diagnosis and eliminating morbidity.